2010
DOI: 10.1071/he10120
|View full text |Cite
|
Sign up to set email alerts
|

Fear and Shame: using theatre to destigmatise mental illness in an Australian Macedonian community

Abstract: Building on previous work, theatre was an effective means of disseminating information and reducing stigma around mental illness in the target community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
1
7
0
1
Order By: Relevance
“…It is also sensitive to gender, religious and social-political issues in the target communities. In the Fear and Shame study [ 36 , 37 ] (Table 1 ), the research team included clinician researchers (with the language skills and cultural background of the community) and bilingual/bicultural research assistants (BRAs). Team building included mentoring clinician researchers and training BRAs to undertake in-language data collection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also sensitive to gender, religious and social-political issues in the target communities. In the Fear and Shame study [ 36 , 37 ] (Table 1 ), the research team included clinician researchers (with the language skills and cultural background of the community) and bilingual/bicultural research assistants (BRAs). Team building included mentoring clinician researchers and training BRAs to undertake in-language data collection.…”
Section: Resultsmentioning
confidence: 99%
“…The Fear and Shame study evaluated an innovative applied theatre intervention to reduce barriers to accessing professional care, low levels of mental health literacy and high levels of stigma around mental illness within the Macedonian community. It followed earlier research in which community members reported a reluctance to use mental health services [ 37 ]. The Chinese GHS study evaluated the language and cultural adaptation of a mainstream programme to inform modifications to increase its accessibility and acceptability.…”
Section: Resultsmentioning
confidence: 99%
“…[UDLA], con existe la materia: "Expresión Corporal y Dramática". Adicionalmente, hay diversas publicaciones sobre este tema, entre otros el documento: Fear and Shame: Using Theatre to Destigmatise Mental Illness in an Australian Macedonian Community (Blignault, et al 2010), según el cual se logró mediante la representación de una obra teatral la visualización, aceptación y tolerancia hacia personas con enfermedades mentales para poder luego implementar acciones de ayuda y mejora; y, el artículo: The Theater and Pedagogy in the History of Education (Sánchez, 2015), publicación que relata la experiencia de los jesuitas al incorporar el teatro en el currículo de escuelas y la representación de dramas con elementos religiosos y profanos contemporáneos con fines didácticos, logrando gran éxito en esta labor.…”
Section: El Teatro Dentro De La Sala De Clasesunclassified
“…Furthermore, theater has been shown as a useful medium for arts-based programs designed to disseminate mental health information and reduce stigma. A study conducted by Blignault et al (2010) analyzed the impact of this strategy and found that audience members showed a positive attitude towards people with mental illness as well as a greater use of mental health services. Koh and Shrimpton (2013) discuss another strategy using an art exhibition by people who have experienced mental illness.…”
Section: Experiential Programsmentioning
confidence: 99%